Positive electrode active material for rechargeable lithium battery, positive electrode including the same, and rechargeable lithium battery including the positive electrode

By using a composite positive electrode active material composed of spinel-structured first particles and layered large and small particles in the positive electrode of a rechargeable lithium battery, the lifespan and stability issues caused by high nickel content are solved, achieving high energy density and improved lifespan characteristics.

CN121011640APending Publication Date: 2025-11-25SAMSUNG SDI CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510639808.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-05-22
Filing Date
2025-05-19
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing rechargeable lithium batteries using lithium composite oxides with high nickel content as the positive electrode active material have lifespan and stability issues.

Method used

A composite positive electrode active material is adopted, consisting of a first particle (spinel structure), a second particle (large layered structure), and a third particle (small layered structure). The first particle occupies a larger proportion, while the second and third particles each occupy an appropriate proportion. The structure stability and conductivity are improved by adhering conductive material to the particle surface.

Benefits of technology

It achieves high energy density and improved lifetime characteristics, including improved capacity retention and reduced resistance increase rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121011640A_ABST
    Figure CN121011640A_ABST
Patent Text Reader

Abstract

The application discloses a positive electrode active material, a positive electrode including the positive electrode active material, and a rechargeable lithium battery including the positive electrode. The positive electrode active material includes first particles including a first lithium composite oxide having a spinel crystal structure, second particles including a second lithium composite oxide having a layered crystal structure, and third particles including a third lithium composite oxide having a layered crystal structure. The average particle size of the second particles is larger than that of the third particles. The first particle has a first weight ratio relative to a total weight of the first particle, the second particle, and the third particle. The second particles have a second weight ratio relative to the total weight. The third particles have a third weight ratio relative to the total weight. The first weight ratio is greater than the sum of the second weight ratio and the third weight ratio.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-reference to related applications

[0002] This application claims priority to Korean Patent Application No. 10-2024-0066327, filed on May 22, 2024, with the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] This disclosure relates to positive electrode active materials, positive electrodes including positive electrode active materials, and rechargeable lithium batteries including positive electrodes. Background Technology

[0004] Batteries generate electrical energy through physical or chemical reactions to supply the generated power. For example, batteries can be used when there is no alternating current (AC) available to power a building, or when direct current (DC) power is expected or required based on the living or usage environment involving one or more suitable electrical and / or electronic devices.

[0005] Batteries typically utilize chemical reactions and are classified into primary and secondary batteries. Primary batteries are consumable batteries, also known as dry cell batteries. In contrast, secondary batteries are rechargeable batteries (e.g., rechargeable lithium batteries) in which oxidation and reduction reactions are repeatedly performed at the positive and negative electrodes. The battery charges when an electric current causes a reduction reaction at the positive electrode, and discharges when an oxidation reaction occurs at the positive electrode. Secondary batteries undergo repeated charge and discharge cycles.

[0006] Lithium composite oxides with high nickel content have attracted considerable attention as positive electrode active materials for rechargeable lithium batteries. These materials possess high energy density, but the high nickel content can lead to a significant reduction in battery life and stability. Summary of the Invention

[0007] Embodiments of this disclosure provide positive electrode active materials for rechargeable lithium batteries having high energy density and improved lifetime characteristics.

[0008] Embodiments of this disclosure provide rechargeable lithium batteries with superior output, increased lifespan, and enhanced capacity retention characteristics.

[0009] According to embodiments of this disclosure, the positive electrode active material may include: a first particle comprising a first lithium composite oxide having a spinel crystal structure; a second particle comprising a second lithium composite oxide having a layered crystal structure; and a third particle comprising a third lithium composite oxide having a layered crystal structure. The average particle size of the second particle may be larger than the average particle size of the third particle. The first particle may have a first weight ratio relative to the total weight of the first, second, and third particles. The second particle may have a second weight ratio relative to the total weight. The third particle may have a third weight ratio relative to the total weight. The first weight ratio may be greater than the sum of the second and third weight ratios.

[0010] According to embodiments of this disclosure, the positive electrode includes the positive electrode active material discussed above.

[0011] According to embodiments of this disclosure, a rechargeable lithium battery includes the positive electrode discussed above. Attached Figure Description

[0012] Figure 1 A simplified conceptual diagram illustrating a rechargeable lithium battery according to an embodiment of the present disclosure is provided.

[0013] Figure 2 A diagram illustrating the positive electrode active material layer according to an embodiment of the present disclosure.

[0014] Figure 3 A cross-sectional view of a large-size lithium composite oxide according to an embodiment of the present disclosure is shown.

[0015] Figure 4 A simplified perspective view is shown to illustrate a rechargeable lithium battery according to an embodiment of the present disclosure. Detailed Implementation

[0016] To fully understand the layout and effects of this disclosure, some embodiments of the disclosure will be described with reference to the accompanying drawings. However, it should be noted that this disclosure is not limited to the exemplary embodiments described below and can be implemented in various forms. Exemplary embodiments are provided only to disclose this disclosure and to enable those skilled in the art to fully understand its scope.

[0017] In this description, when an element is referred to as being on another element, the element may be directly on the other element, or an intervening element may exist between the two. In the accompanying drawings, the dimensions (e.g., thickness) of some components are exaggerated for the purpose of effectively explaining the technical content. Throughout the specification, the same reference numerals refer to the same elements.

[0018] Some embodiments detailed in this description will be described with reference to cross-sectional and / or plan views, which are ideal exemplary views in this disclosure. In the drawings, the dimensions (e.g., thickness) of layers and regions are exaggerated for the purpose of effectively explaining the technical content. Accordingly, the regions exemplarily illustrated in the drawings have general properties, and the shapes of the regions exemplarily illustrated in the drawings are used to exemplarily disclose specific shapes, but are not limited to the scope of this disclosure. It will be understood that although the terms “first,” “second,” “third,” etc., may be used herein to describe various elements, these elements should not be limited by these terms. These terms are used only to distinguish one element from another. Some embodiments explained and illustrated herein include supplementary embodiments thereof.

[0019] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit this disclosure. As used herein, the singular form is intended to include the plural form as well. The terms “comprises / includes” and / or “comprising / including” as used in the specification do not exclude the presence or addition of one or more other components.

[0020] Figure 1 A simplified conceptual diagram illustrating a rechargeable lithium battery according to an embodiment of the present disclosure is shown. (Reference) Figure 1 A rechargeable lithium battery may include a positive electrode 100, a negative electrode 200, an electrolyte 300, and a separator 400.

[0021] The positive electrode 100 and the negative electrode 200 may be spaced apart from each other across the diaphragm 400. The diaphragm 400 may be disposed between the positive electrode 100 and the negative electrode 200. The positive electrode 100, the negative electrode 200, and the diaphragm 400 may be in contact with the electrolyte 300. The positive electrode 100, the negative electrode 200, and the diaphragm 400 may be immersed in the electrolyte 300.

[0022] The electrolyte 300 can be used as a medium for transporting lithium ions between the positive electrode 100 and the negative electrode 200. Lithium ions in the electrolyte 300 can pass through the membrane 400 to move toward the positive electrode 100 or the negative electrode 200.

[0023] The positive electrode 100 may include a first current collector COL1 and a positive electrode active material layer AML1 on the first current collector COL1. The first current collector COL1 may include one or more metals, such as aluminum, copper, nickel-plated copper, stainless steel, nickel, titanium, palladium, and aluminum-cadmium alloys. The shape of the first current collector COL1 may be like a film, sheet, foil, mesh, net, porous material, foam, or nonwoven fabric.

[0024] The positive electrode active material AML1 may include a binder, a conductive material, and the positive electrode active material itself. Based on the total amount of the positive electrode active material layer AML1, the content of the positive electrode active material may be from about 80 wt% to about 99 wt%, for example, from about 85 wt% to about 98 wt%. The positive electrode active material may be a lithium-ion source. The positive electrode active material may be a lithium transition metal oxide, which may include not only lithium but also at least one transition metal. References will follow below. Figure 2 and Figure 3 The positive electrode active material of this disclosure according to some embodiments is described in more detail.

[0025] The conductive material provides conductivity to the positive electrode active material layer AML1. The conductive material may include at least one of carbon-based materials (e.g., graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lampblack, thermal cracking black, and carbon fibers), metal powders, metal fibers, conductive whiskers, conductive metal oxides, conductive polymers, and combinations thereof. Based on the total weight of the positive electrode active material layer AML1, the content of the conductive material may be from about 1 wt% to about 30 wt%.

[0026] An adhesive can increase the adhesion between the positive electrode active material and the first current collector COL1. For example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, and combinations thereof. Based on the total weight of the positive electrode active material layer AML1, the adhesive content may be from about 1 wt% to about 30 wt%.

[0027] The negative electrode 200 may include a second current collector COL2 and a negative electrode active material layer AML2 on the second current collector COL2. The description of the second current collector COL2 may be the same as or similar to the description of the first current collector COL1. The second current collector COL2 may include the same or different metals as the metals included in the first current collector COL1. The second current collector COL2 may have the same or different shapes as the first current collector COL1.

[0028] The negative electrode active material layer AML2 may include a binder, a conductive material, and a negative electrode active material. The binder and conductive material may be the same as those discussed above for the positive electrode active material layer AML1. Based on the total weight of the negative electrode active material layer AML2, the content of the negative electrode active material may be from about 80 wt% to about 99 wt%, for example, from about 85 wt% to about 98 wt%. The negative electrode active material may include at least one of carbonaceous materials, lithium metal, lithium metal compounds, silicon, silicon compounds, tin, and tin compounds. Metal oxides with a potential less than about 2 V (such as TiO2 or SnO2) may also be used as negative electrode active materials. Carbonaceous materials may include one or more of low-crystallinity carbon and high-crystallinity carbon.

[0029] The diaphragm 400 may comprise a porous polymer membrane formed of a polyolefin polymer, such as ethylene homopolymer, propylene homopolymer, ethylene-butene copolymer, ethylene-hexene copolymer, and ethylene-methacrylate copolymer. The diaphragm 400 may comprise a single diaphragm of porous polymer membranes or a stacked diaphragm of multiple porous polymer membranes. In embodiments of this disclosure, the diaphragm 400 may comprise a common porous nonwoven fabric, such as high-melting-point glass fiber or polyethylene terephthalate fiber.

[0030] Electrolyte 300 may include having A + B - Salts with a structure of . A + May include selections from Li + Na + and K + At least one alkali metal cation in B. - May include selections from F - Cl - ,Br - I - NO3 - N(CN)2 - BF4 - ClO4 - AlO4 - AlCl4 - PF6 - SbF6 - AsF6 - BF2C2O4 - BC4O8 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - C4F9SO3 -CF3CF2SO3 - (CF3SO2)2N - (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - and (CF3CF2SO2)2N - At least one anion in it.

[0031] In embodiments of this disclosure, the electrolyte 300 can be used by dissolving the salt in an organic solvent. The organic solvent may include propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, ethylene glycol dimethyl ether, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone, or any mixture thereof.

[0032] According to some disclosed embodiments, commonly used housings in the art can be used as the housing of rechargeable lithium batteries, and there are no limitations on the appearance depending on the application of the battery. For example, the housing of a rechargeable lithium battery can be cylindrical, prismatic, pouch-shaped, or coin-shaped.

[0033] Figure 2 A diagram illustrating the positive electrode active material layer according to an embodiment of the present disclosure. (Reference) Figure 2 The positive electrode active material layer may include multiple first particles PTC1, multiple second particles PTC2, and multiple third particles PTC3.

[0034] The first particle PTC1 may have a first average particle size APD1. The second particle PTC2 may have a second average particle size APD2, and the third particle PTC3 may have a third average particle size APD3. The third average particle size APD3 may be smaller than the second average particle size APD2. The third average particle size APD3 may be smaller than the first average particle size APD1. The first average particle size APD1 may be equal to or smaller than the second average particle size APD2.

[0035] The first average particle size APD1 can be in the range of about 1.0 μm to about 10.0 μm. The second average particle size APD2 can be in the range of about 10.0 μm to about 20.0 μm. The third average particle size APD3 can be in the range of about 1.0 μm to about 5.0 μm. The term "average particle size" or D is used in this disclosure. 50 The average particle size can refer to the particle size in the particle size distribution obtained from the particle volume when the cumulative volume percentage corresponds to 50% by volume. The average particle size can be measured, for example, by a particle size analyzer (PSA). In this disclosure, the second particle PTC2 can be referred to as a large particle, and the third particle PTC3 can be referred to as a small particle.

[0036] Figure 3 A second particle PTC2 is illustrated according to an embodiment of this disclosure. Reference Figure 3 The shape of the second particle PTC2 can resemble that of a secondary particle SDP in which multiple primary particles PRP are aggregated. The multiple primary particles PRP can be arranged radially from the center to the surface of the secondary particle SDP (radial arrangement).

[0037] Refer again Figure 2 The third PTC3 particle may have a granular or spherical shape. In embodiments of this disclosure, the third PTC3 particle may have a single particle shape. A single particle shape may include a primary particle shape or a secondary particle shape obtained by aggregating several primary particles. A single particle shape may include one grain or several grains. A grain may be the smallest unit in which the lithium composite oxide has a single crystal orientation. For example, the third PTC3 particle may include a primary particle, a single particle, or a secondary particle in which multiple primary particles are aggregated.

[0038] The positive electrode active material according to embodiments of this disclosure may have a bimodal shape comprising large particles (e.g., the second particle PTC2) and small particles (e.g., the third particle PTC3) with different average particle sizes. The small particles can fill the pores between the large particles, thus the positive electrode active material may have an increased integration density. For example, the positive electrode active material according to some embodiments of this disclosure may have a relatively high energy density per unit volume.

[0039] The first PTC1 particle may include a first lithium composite oxide. The first lithium composite oxide may have a spinel crystal structure and may be represented by chemical formulas 1 to 3.

[0040] Chemical Formula 1:

[0041] Li a M2O4

[0042] In Chemical Formula 1, 0.9 ≤ a ≤ 1.1, and M may be or include one or more of manganese and non-manganese elements of Groups 4 to 13.

[0043] Chemical Formula 2:

[0044] Li a Mn b M1 c M2 d O4

[0045] In Chemical Formula 2, 0.9 ≤ a ≤ 1.1, 0 < b ≤ 2.0, 0 ≤ c < 2.0, 0 ≤ d < 0.1, and b + c + d = 2; and M1 and M2 may be different from each other and may each independently be or include at least one selected from Co, Ni, V, Cr, Fe, Zr, Re, Al, B, Ge, Ru, Sn, Ti, Nb, Mo, and Pt.

[0046] Chemical Formula 3:

[0047] Li a Mn b Co c M2 d O4

[0048] In Chemical Formula 3, 0.9 ≤ a ≤ 1.1, 0 < b < 2.0, 0 < c < 2.0, 0 ≤ d < 0.1, and b + c + d = 2; and M2 may be or include at least one selected from Ni, V, Cr, Fe, Zr, Re, Al, B, Ge, Ru, Sn, Ti, Nb, Mo, and Pt.

[0049] The second particle PTC2 may include a second lithium composite oxide, and the third particle PTC3 may include a third lithium composite oxide. The second lithium composite oxide and the third lithium composite oxide may each have a layered crystal structure and may each independently be represented by Chemical Formulas 4 to 7.

[0050] Chemical Formula 4:

[0051] Li a M'O2

[0052] In Chemical Formula 4, 0.9 ≤ a ≤ 1.1, M' may be or include one or more of nickel and non-nickel elements of Groups 4 to 13, and the amount of nickel in M' may be equal to or greater than about 70 at% and less than 100 at%.

[0053] Chemical Formula 5:

[0054] Li a Ni b M3 c M4 d M5e O2

[0055] In Chemical Formula 5, 0.9 ≤ a ≤ 1.1, 0.7 ≤ b < 1.0, 0 < c < 0.3, 0 < d < 0.3, 0 ≤ e < 0.1, and b + c + d + e = 1; M3, M4, and M5 can be different from each other and can each independently be or include at least one selected from Mn, V, Cr, Fe, Co, Zr, Re, Al, B, Ge, Ru, Sn, Ti, Nb, Mo, and Pt.

[0056] Chemical Formula 6:

[0057] Li a Ni b Co c Mn d M5 e O2

[0058] In Chemical Formula 6, 0.9 ≤ a ≤ 1.1, 0.7 ≤ b < 1.0, 0 < c < 0.3, 0 < d < 0.3, 0 ≤ e < 0.1, and b + c + d + e = 1; and M5 can be or include at least one selected from V, Cr, Fe, Zr, Re, Al, B, Ge, Ru, Sn, Ti, Nb, Mo, and Pt.

[0059] Chemical Formula 7:

[0060] aLi2MnO3-(1-a)LiM'O2

[0061] In Chemical Formula 7, 0 < a < 1, and M' can be or include at least one selected from Ni, Co, Mn, V, Cr, Fe, Zr, Re, Al, B, Ge, Ru, Sn, Ti, Nb, Mo, and Pt.

[0062] In this embodiment, relative to the total weight of the first PTC1, second PTC2, and third PTC3 particles, the first PTC1 particle in the positive electrode active material may have a weight ratio of about 60 wt% to about 90 wt%, about 60 wt% to about 80 wt%, or about 70 wt% to about 80 wt%. Relative to the total weight of the first PTC1, second PTC2, and third PTC3 particles, the second PTC2 particle in the positive electrode active material may have a weight ratio of about 5 wt% to about 30 wt%, about 7 wt% to about 30 wt%, or about 10 wt% to about 21 wt%. Relative to the total weight of the first PTC1, second PTC2, and third PTC3 particles, the third PTC3 particle in the positive electrode active material may have a weight ratio of about 3 wt% to about 12 wt%, or about 3 wt% to about 9 wt%. The second weight ratio may be greater than the third weight ratio. When the first PTC1, the second PTC2, and the third PTC3 have these weight ratios, the rechargeable lithium battery, including the positive electrode active material, can have improved output and lifespan properties.

[0063] Because the first PTC1 particle, which exhibits excellent structural stability, comprises approximately 60 wt% to approximately 90 wt% of the positive electrode active material, the positive electrode active material can possess superior structural stability. Since the positive electrode active material includes approximately 10 wt% to approximately 40 wt% of the second PTC2 particle and the third PTC3 particle (which have a high nickel content and a layered crystal structure), this positive electrode active material can exhibit improved lifetime and capacity characteristics compared to a positive electrode active material containing only the first PTC1 particle.

[0064] Return to reference Figure 2 The positive electrode active material layer may further include a conductive material CDA between the first particle PTC1, the second particle PTC2, and the third particle PTC3. The conductive material CDA may be adhered to (or provided) on the surface of each of the first particle PTC1, the second particle PTC2, and the third particle PTC3. The density of the conductive material CDA on the first particle PTC1 may be greater than the density of the conductive material CDA on the second particle PTC2. The density of the conductive material CDA on the first particle PTC1 may be greater than the density of the conductive material CDA on the third particle PTC3. In some embodiments, the conductive material CDA may be more concentrated on the first particle PTC1 than on the second particle PTC2 and the third particle PTC3.

[0065] In this disclosure, the density of the conductive material CDA can be defined as the amount of conductive material CDA adhering to the surface of the active material particles per unit surface area. Since the conductive material CDA is more concentrated around the particles occupying a high weight ratio of spinel crystal structure, the conductivity of the positive electrode active material layer according to this disclosure can be improved.

[0066] In addition to the uses of the positive electrode active material according to some embodiments of this disclosure, Figure 1 The positive electrode 100 can be manufactured using typical positive electrode manufacturing methods. For example, the positive electrode active material, binder, and conductive material of this disclosure can be dissolved or dispersed in a solvent to prepare a mixture. The binder and conductive material can be combined with the above-mentioned active material in a solvent. Figure 1 The same process is discussed in the positive electrode active material layer AML1. The mixture can be coated onto the first current collector COL1, then dried and pressed to manufacture the positive electrode 100.

[0067] The solvent may be a solvent commonly used in the art, for example, it may include at least one of dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, water, and combinations thereof.

[0068] Figure 4 A simplified perspective view is shown to illustrate a rechargeable lithium battery according to an embodiment of the present disclosure. References Figure 4 A rechargeable lithium battery may include a positive electrode 100, a negative electrode 200, and a separator 400. Figure 4 The descriptions of the positive electrode 100, negative electrode 200, and diaphragm 400 are consistent with those above. Figure 1 The discussion is essentially the same as that in rechargeable lithium batteries.

[0069] Figure 4 The positive electrode 100, negative electrode 200, and separator 400 can be wound or folded to form an electrode assembly. The electrode assembly can be housed within a battery housing 500. The electrode assembly may include multiple electrode assemblies. The separator 400 may be provided between the electrode assemblies. The battery housing 500 may provide electrode assemblies stacked sequentially. The battery housing 500 may be filled with an electrolyte (see...). Figure 1 (300). The battery casing 500 can be sealed with a cover assembly 600. The battery casing 500 according to embodiments of the present disclosure may have a cylindrical, prismatic, or pouch shape. The rechargeable lithium battery according to embodiments of the present disclosure can be used in devices such as laptop computers, smartphones, or electric vehicles.

[0070] The following description will focus on some embodiments of this disclosure. These embodiments are provided to aid in understanding this disclosure and are not intended to limit its scope.

[0071] Preparation 1: First lithium composite oxide with spinel crystal structure

[0072] 0.170 g of MnSO4·H2O and 0.0228 g of (NH4)2S2O8 were dissolved in 100 ml of distilled water, and sulfuric acid was added to adjust the pH to 1. The reaction was then carried out at 130 °C for 10 hours to obtain a solid precipitate. The precipitate was washed several times with distilled water and dried at 300 °C for 3 hours to prepare solid MnO2 with an average particle size of 1 μm.

[0073] Li2CO3 and prepared MnO2 were mixed at a molar ratio of Li:Mn = 1:2, and then heated at 600℃ for 10 hours to synthesize LiMn2O4 particles with an average particle size of 1 μm.

[0074] Preparation 2: Large-particle lithium composite oxide with layered crystal structure

[0075] Large-size precursors were prepared using a co-precipitation method. The following steps were used to prepare nickel-based metal hydroxides (Ni...) as large-size precursors. 0.90 Co 0.07 Al 0.03 (OH)2).

[0076] As raw materials for nickel-based metal hydroxides, nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O), and aluminum sulfate (Al2(SO4)3·H2O) were mixed in a molar ratio of 90:7:3 and dissolved in distilled water as a solvent to prepare a mixed solution of the metal raw materials. A dilute solution of ammonium hydroxide (NH4OH) and sodium hydroxide (NaOH) as a precipitant were prepared to form a complex. Then, the mixed solution of the metal raw materials, ammonium hydroxide, and sodium hydroxide were introduced into a reactor. Sodium hydroxide was added to maintain the pH of the mixture in the reactor. The reaction proceeded for approximately 20 hours while the mixture in the reactor was stirred.

[0077] The slurry solution in the reactor was filtered and rinsed with high-purity distilled water. The rinsed material was dried in a hot air oven at 190°C for 24 hours to obtain a large-size precursor (Ni) with a particle size of approximately 18 μm. 0.90 Co 0.07 Al 0.03 Powder of (OH)2).

[0078] The large-size precursor and anhydrous lithium hydroxide (LiOH) were dry-mixed using a Henschel mixer. Lithium and transition metals were mixed at a molar ratio of approximately 1:1. The transition metals were the total amount of transition metals (Ni+Co+Al) contained in the large-size precursor. The mixture was heat-treated at approximately 900°C for 10 hours under an oxygen atmosphere (first calcination process) to synthesize second particles as a second lithium composite oxide. The second particles were pulverized using a jet mill at a pressure of 3 bar.

[0079] Preparation 3: Small-sized lithium composite oxides with layered crystal structures

[0080] A co-precipitation method was used to prepare small-sized precursors. The following steps were used to prepare nickel-based metal hydroxides (Ni...) as small-sized precursors. 0.90 Co 0.07 Mn 0.03 (OH)2).

[0081] As raw materials for nickel-based metal hydroxides, nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O), and manganese sulfate (MnSO4·H2O) are mixed in a molar ratio of 90:7:3 and dissolved in distilled water as a solvent to prepare a mixed solution of metal raw materials. The mixed solution of metal raw materials, ammonium hydroxide, and sodium hydroxide are introduced into a reactor, and then the reaction is carried out.

[0082] The slurry solution in the reactor was filtered and rinsed with high-purity distilled water. The rinsed material was dried in a hot air oven at 210°C for 24 hours to obtain a small-sized precursor (Ni) with a size of approximately 3 μm. 0.90 Co 0.07 Mn 0.03 Powder of (OH)2).

[0083] The small-sized precursor and anhydrous lithium hydroxide (LiOH) were dry-mixed using a Henschel mixer. Lithium and transition metals were mixed at a molar ratio of approximately 1:1. In this case, the transition metals were the total amount of transition metals (Ni+Co+Mn) contained in the small-sized precursor. The mixture was heat-treated at approximately 750°C for 15 hours under an oxygen atmosphere (second calcination process) to synthesize third particles as a third lithium composite oxide. The third particles were pulverized using a jet mill at a pressure of 3 bar.

[0084] Implementation Method 1: Preparation of Composite Positive Electrode Active Material

[0085] The first particle of preparation 1, the second particle of preparation 2, and the third particle of preparation 3 are mixed in a weight ratio of 60:28:12 to obtain a powder of composite positive electrode active material.

[0086] Implementation Method 2

[0087] The first particle of preparation 1, the second particle of preparation 2, and the third particle of preparation 3 are mixed in a weight ratio of 70:21:9 to obtain a powder of composite positive electrode active material.

[0088] Implementation Method 3

[0089] The first particle of preparation 1, the second particle of preparation 2, and the third particle of preparation 3 are mixed in a weight ratio of 80:14:6 to obtain a powder of composite positive electrode active material.

[0090] Implementation Method 4

[0091] The first particle of preparation 1, the second particle of preparation 2, and the third particle of preparation 3 are mixed in a weight ratio of 90:7:3 to obtain a powder of composite positive electrode active material.

[0092] Comparative Example 1

[0093] The first particle of preparation 1, the second particle of preparation 2, and the third particle of preparation 3 are mixed in a weight ratio of 50:35:15 to obtain a powder of composite positive electrode active material.

[0094] Comparative Example 2

[0095] The first particle of preparation 1, the second particle of preparation 2, and the third particle of preparation 3 are mixed in a weight ratio of 95:3.5:1.5 to obtain a powder of composite positive electrode active material.

[0096] Comparative Example 3

[0097] The powder of the positive electrode active material is obtained using only the first particle from Preparation 1.

[0098] Manufacturing of positive electrode

[0099] 95 wt% of positive electrode active material, 3 wt% of polyvinylidene fluoride as a binder, and 2 wt% of carbon black as a conductive material were mixed in N-methylpyrrolidone solvent to obtain a positive electrode active material slurry. The positive electrode active material slurry was coated onto an aluminum current collector and dried, and then pressed to manufacture the positive electrode.

[0100] Manufacturing of negative electrode

[0101] A negative electrode active material slurry was prepared by mixing 95 wt% graphite, 3 wt% binder (PVdF), and 2 wt% conductive material (carbon black) in an N-methylpyrrolidone solvent. The negative electrode active material slurry was coated onto a copper current collector and dried, and then pressed to manufacture the negative electrode.

[0102] Manufacturing of rechargeable lithium batteries

[0103] The manufactured positive and negative electrodes were used to fabricate a single coin cell. A polypropylene layer (Celgard 3510) was used as the separator. 1.3M LiPF6 was used as the electrolyte, dissolved in a mixed solvent containing ethylene carbonate (EC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC) in a volume ratio of 3:5:2.

[0104] Assessment 1: Lifetime Characteristics

[0105] The lifespan characteristics of rechargeable lithium batteries manufactured using the positive electrode active materials of Embodiments 1 to 4 and Comparative Examples 1 to 3 were evaluated.

[0106] Rechargeable lithium-ion batteries were subjected to 1,000 cycles of continuous charge and discharge at 45°C under 0.5C charging and discharging conditions, and then the capacity retention after 1,000 cycles was evaluated. The charging process was performed in constant current-constant voltage (CC-CV) mode with a cutoff voltage of 4.25V and a cutoff current of 0.05C. The discharging process was performed in constant current mode with a cutoff voltage of 2.5V. The capacity retention was calculated according to Equation 1, and the results are listed in Table 1.

[0107] Mathematical Equation 1:

[0108] Capacity retention (%) = [Discharge capacity at cycle 1,000 / Discharge capacity at cycle 1] × 100

[0109] Table 1

[0110]

[0111] Referring to Table 1, it can be observed that the capacity retention rate of the rechargeable lithium battery according to the embodiment is greater than that of the rechargeable lithium battery according to the comparative example. For example, it can be determined that when the weight ratio of the first particle, the second particle, and the third particle falls within a specific range, an excellent capacity retention rate is achieved.

[0112] Evaluation 2: Resistance Characteristics

[0113] The resistance characteristics of rechargeable lithium batteries manufactured using the positive electrode active materials of Embodiments 1 to 4 and Comparative Examples 1 to 3 were evaluated.

[0114] The rechargeable lithium battery was subjected to 1,000 cycles of continuous charge and discharge at 45°C under 0.5C charging and discharging conditions, and the rate of increase in resistance (DC-IR) after 1,000 cycles was then evaluated. The charging process was performed in constant current-constant voltage (CC-CV) mode with a cutoff voltage of 4.25V and a cutoff current of 0.05C, and the discharging process was performed in constant current mode with a cutoff voltage of 2.5V. The rate of increase in resistance was calculated according to mathematical equation 2, and the results are listed in Table 2.

[0115] Mathematical Equation 2

[0116] DC-IR increase rate (%) = [DC-IR (mΩ) at the 1,000th cycle / DC-IR (mΩ) at the 1st cycle] × 100

[0117] Table 2

[0118]

[0119] Referring to Table 2, it can be observed that the resistance increase rate of the rechargeable lithium battery according to the embodiment is less than that of the rechargeable lithium battery according to the comparative example. For example, it can be determined that a reduced resistance increase rate is achieved when the weight ratio of the first particle, the second particle, and the third particle falls within a specific range.

[0120] In the positive electrode active material for a rechargeable lithium battery according to the present disclosure, the weight ratio of the first particle having a spinel crystal structure may be greater than the sum of the weight ratios of the second and third particles each having a layered crystal structure.

[0121] Therefore, the positive electrode active material of this disclosure can have high energy density and improved lifetime characteristics. Rechargeable lithium batteries incorporating the positive electrode active material of this disclosure can exhibit improved capacity characteristics and increased lifetime properties.

Claims

1. A positive electrode active material, comprising: A first particle, comprising a first lithium composite oxide having a spinel crystal structure; A second particle, comprising a second lithium composite oxide having a layered crystal structure; And A third particle, comprising a third lithium composite oxide having a layered crystal structure, Wherein the average particle size of the second particle is greater than the average particle size of the third particle, Wherein the first particle has a first weight ratio with respect to the total weight of the first particle, the second particle and the third particle, Wherein the second particle has a second weight ratio with respect to the total weight, Wherein the third particle has a third weight ratio with respect to the total weight, and Wherein the first weight ratio is greater than the sum of the second weight ratio and the third weight ratio.

2. The positive electrode active material according to claim 1, wherein the average particle size of the second particle is four to twenty times the average particle size of the third particle.

3. The positive electrode active material according to claim 1, wherein each of the second particles comprises secondary particles, and the secondary particles comprise a plurality of primary particles, Wherein the primary particles are radially arranged from the center to the surface of the second particle.

4. The positive electrode active material according to claim 1, wherein the first lithium composite oxide is represented by Chemical Formula 1: Li a M2O4 Where 0.9 ≤ a ≤ 1.1, and M comprises manganese and one or more non-manganese elements of Group 4 to Group 13.

5. The positive electrode active material according to claim 1, wherein the first lithium composite oxide is represented by Chemical Formula 2: Li a Mn b M1 c M2 d O4 Where 0.9 ≤ a ≤ 1.1, 0 < b ≤ 2.0, 0 ≤ c < 2.0, 0 ≤ d < 0.1, and b + c + d = 2, and M1 and M2 are different from each other and each independently comprises at least one selected from Co, Ni, V, Cr, Fe, Zr, Re, Al, B, Ge, Ru, Sn, Ti, Nb, Mo and Pt.

6. The positive electrode active material according to claim 1, wherein the first lithium composite oxide is represented by Chemical Formula 3: Li a Mr b Co c M2 d O4 ​ ​ Li a M'O2 ​ ​ Li a Ni b M3 c M4 d M5 e O2 where 0.9 ≤ a ≤ 1.1, 0.7 ≤ b < 1.0, 0 < c < 0.3, 0 < d < 0.3, 0 ≤ e < 0.1, and b + c + d + e = 1, and M3, M4, and M5 are different from each other and each independently includes at least one selected from Mn, V, Cr, Fe, Co, Zr, Re, Al, B, Ge, Ru, Sn, Ti, Nb, Mo, and Pt.

9. The positive electrode active material according to claim 1, wherein the second lithium composite oxide and the third lithium composite oxide are each independently represented by Chemical Formula 6: Li a Ni b Co c Mr d M5 e O2 where 0.9 ≤ a ≤ 1.1, 0.7 ≤ b < 1.0, 0 < c < 0.3, 0 < d < 0.3, 0 ≤ e < 0.1, and b + c + d + e = 1, and M5 includes at least one selected from V, Cr, Fe, Zr, Re, Al, B, Ge, Ru, Sn, Ti, Nb, Mo, and Pt.

10. The positive electrode active material according to claim 1, wherein the second lithium composite oxide and the third lithium composite oxide are each independently represented by Chemical Formula 7: aLi2MnO3-(1-a)LiM'O2 where 0 < a < 1, and M' includes at least one selected from Ni, Co, Mn, V, Cr, Fe, Zr, Re, Al, B, Ge, Ru, Sn, Ti, Nb, Mo, and Pt.

11. The positive electrode active material according to claim 1, wherein the first weight ratio is 60 wt% to 90 wt%.

12. The positive electrode active material according to claim 1, wherein the second weight ratio is greater than the third weight ratio. The positive electrode active material according to claim 1, wherein the second weight ratio is 5 wt% to 30 wt%, and the third weight ratio is 3 wt% to 12 wt%.

14. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 13.

15. A rechargeable lithium battery comprising the positive electrode according to claim 14.

Citation Information

Cited By

  • Positive electrode active material, positive plate, battery, battery pack, electric equipment and quality control method of positive electrode active material

    CN121260785A